Dampak Sunat Terhadap Status Kesehatan Perempuan di Pulau Buru - D. Tauho, Kristiani; Tampubolon, Rifatolistia; Solissa, Oklin (Jurnal Keperawatan Muhammadiyah, 2024)
Background The female circumcision is the act of removing or cutting the clitoris, who can make the impact physically or psychologically for women. Research objectives: research is aimed to determine the impact of circumcising girls in fertile women health status on the island of rush. Methods: research methods it uses quantitative methods.Mngeswaen research sites in the village, the inclusion of women have done circumcision ( toho wae ) 15-45 years of age.The number of respondents determined based on respondents were 59 slovin formula. Result: management, circumcision Mngeswaen had an impact them were found in the village of: do not feel pain, whitish, bleeding and depressed, other positive impact to women who married the sound and pain to an intimate relationship.This study did not found the impact on health external serious complications In terms of health angle of view, care for healing after circumcision only done traditionally which treatments are traditionally and maintenance is not a medical workers but a mama biang for elder is decades performs circumcision is. As for traditional medicines used by the lahiglangan of mama biang, barut, Olbeu, and grains. Conclusion: expected health workers do education about the risk of the female circumcision and to ensure that the public can be modified without reducing cultural values and beliefs that embraced by locals.